P–T–t evolution of an Early Silurian medium-grade shear zone on the west side of the Famatinian magmatic arc, Argentina: Implications for the assembly of the Western Gondwana margin - Castro, Brigida Marta Ester (2008)
The geodynamic evolution of the proto-Andean margin of Gondwana during the Paleozoic was characterized by repeated subduction processes associated with the docking of several terranes, including the Cuyania–Precordillera terrane and the Chilenia terrane, and the development of the calc–alkaline Famatinian continental magmatic arc. In the Sierra de La Huerta (30°56′–31°29′ S and 67°17′–67°32′ W), at the southwestern end of the Western Sierras Pampeanas, some mafic to ultramafic igneous bodies belonging to the Famatinian arc were affected by regional metamorphism of the medium-pressure granulite facies (7–7.5 kbar, ≈ 850 °C). After this regional metamorphism, local mylonitization under amphibolite facies along discrete NW–SE to NNW–SSE striking ductile shear zones occurred. A 40Ar/39Ar plateau age of 432 ± 4 Ma was obtained on rather homogeneous hornblende porphyroclasts from a metagabbro mylonite. The textures and mineral chemistry of the mylonitized metagabbro allow its P–T–t evolution from magmatic crystallization to mylonitization to be constrained. Geochronological data obtained from mylonite provide evidence that orogenesis was active at least until the Early Silurian. This deformational event would have been related to uplift and decompression during the later stages of the orogenesis, probably associated with the accretion of the Precordillera terrane to the southwestern Gondwana margin.